Effect of Dead Sea Climatotherapy on Psoriasis; A Prospective Cohort Study - Emmanuel, Thomas; Lybæk, Dorte; Johansen, Claus; Iversen, Lars (Frontiers in Medicine, 2020)
Background: Dead Sea climatotherapy (DSC) is a treatment option for psoriasis in Denmark. However, the response to DSC has not been particularly well studied. Aim: We sought to determine effectiveness and response duration of DSC on psoriasis-related outcome parameters. Methods: Eighteen patients participated in a 4-week treatment program in Ein Gedi in Israel. Treatment, consisting of sun exposure and bathing, was individualized. Results: DSC was associated with a mean 13.0-point reduction (88%) in Psoriasis Area and Severity Index and a mean reduction of 2.3 (76.7%) on the 5-point Investigator's Global Assessment Scale. Furthermore, patients’ quality of life improved measured by the Dermatology Quality of Life Index and EuroQol 5D index values. The mean time from treatment end to reappearance of visible skin symptoms was 93.8 days (SD: 62.5, range: 31-219 days). Conclusions: Our results confirm that DSC has an immediate effect on skin manifestations and improves quality of life, but long-term disease control is not observed.